El Tratado de Libre Comercio entre Chile y Estados Unidos - Ramos, Joseph; Ulloa Urrutia, Alfie (Estudios Internacionales, 2003)
On June 6, 2003, Chile and the United States signed a Free Trade Agreement (FTA), which fully liberalizes trade in goods and establishes broad commitments in other matters. This achievement is not isolated and must be considered as the consolidation of a Chilean policy based on free trade and its institutional solidity. In this paper a chronology of the twelve years elapsed between the first announcement and the last negotiating round of the Treaty is presented and then some theoretical considerations regarding the benefits of opening with regarding Chile are analyzed and some comments are made about certain chapters of the Agreement.